KAJIAN PRODUKSI JAGUNG DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA (STUDI KASUS DI KABUPATEN SELUMA PROPINSI BENGKULU) - Cahyadinata, Indra; Iryansyah, Risqie (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2010)
This research was aimed to define the corn farmer's behaviour in Seluma Regency of Bengkulu Province on inputs and outputs allocation, and determine of production factors influencing corn production. The research was located in three villages in Seluma Regency, namely Riak Siabun, Sido Luhur, and Sumber Arum. Sixty two farmers were selected using stratified random sampling method. In this research, the analitical description was used to analyse farmer behaviour. In order to determine the input and output allocation of the corn productions, this research used the function of production Cobb-Douglas approach. The result showed found that the behaviour of the farmers to choose corn was due to the corn was easy to sell and cultivate. However, the farmers found that it is hard to access some production factors, such as seed, fertilizer, and pesticide. Their prices were also high, and these were contradicted to the product's price which was low. Tis research also found that land area is the main factor that has a significant impacts on production while other factors were not.